In Vitro Assessment of Miltefosine Activity Against Promastigotes and Axenic Amastigotes of Leishmania tropica - Zghair , Khawla H. (Iraqi Journal of Science, 2022)
Leishmaniasis is a worldwide disease still treated with expensive compounds that present severe side effects, and are frequently ineffective emphasizing the importance to search effective compounds against this disease. Miltefosine drug (HePC) that used as antitumor agent has been used against Leishmania tropica in two forms promastigote and axenic amastigote in vitro conditions. Different concentrations (5, 10, 15, 20, 25 and 30 μM) of HePC were performed and exposed to both parasite forms in comparison to sodium stibogluconate (Sb) drug. Parasites viability then was determined using MTT assay after 12, 24, and 48hr of exposure. DNA was extracted from treated and untreated parasites after 48hr of exposure and qualitative analysis of the total genomic DNA fragmentation was carried out through using agarose gel electrophoresis.The IC50 of HePC and Sb were 17.07 and 25.72 μM against L. tropica promastigotes, respectively, while, the IC50 of them were 18.08 and 21.29μM against axenic amastigotes respectively. Fragmented DNA in agarose gel electrophoresis was revealed in both parasite forms exposed to all used concentrations of HePC. These results showed the significant activity of miltefosine against the viability of L. tropica promastigotes and axenic amastigotes.